(untitled) (Journal of the College of Basic Education, 2024)
In this work, colloidal AgNPs have been synthesized through chemical reduction (cold method) with sodium borohydride (NaBH4) as the reducing agent, and the solution was modified by adding 0.1 ml of both NH3 and HNO3 solutions to the various pH values. The silver nanoparticles colloidal suspension was then preserved utilizing polyvinylpyrrolidone (PVP). The impact of pH on the AgNPs’ size was discussed, and the surface plasmon resonance (SPR) behavior of AgNPs in aqueous sols prepared at various pH values varies. Surface plasmon peaks at around (434,426, 410 nm) wavelengths and different pH levels (5, 7, and11). For the reaction system; when changing different Ph values, the silver nanoparticles size scale was determined. At high pH, compared to low pH, smaller silver nanoparticles were obtained. Plasmon resonance shows a difference in the size of AgNPs. Ag NPs have a cubic polycrystalline structure, according to X-Ray diffraction (XRD). The Energy Dispersive X-Ray (EDX), Atomic Force Microscope (AFM), and Scanning Electron Microscope (SEM) were used to characterize Ag NPs.